Financial Performance Analysis Of Sub-Sector Food And Stables Retailing Companies Listed In Indonesia Stock Exchange In 2022 - Bagas, Wayan; Susena, Karona Cahya; Astuty, Kamelia (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
The purpose of this study is to find out the Financial Performance Analysis of Sub-Sector Food and Stables Retailing Companies listed on the Indonesian Stock Exchange in 2022. The method of data collection used is to use secondary data taken from the Company's financial statements published at https://www.idx.co.id/) and the respective company's website. With analysis methods using liquidity ratio (CR,QR), solvency ratio(DER,DAR), activity ratio 9RTO,ITO) , and profitability ratio (NPM, ROI) with financial performance indicators based on industry standards.According to the analysis, on the liquidity ratio, PT DMND has the best financial performance for CR of 3.26 times while for QR is PT KMDS with the ratio of 1.99 times. On the solvency ratio the best performance of DAR and DER is PT KMDS, with the magnitude of ratio respectively 26,07% and 20,68%. On the actisvity ratio, PT MPPA has the finest performance for RTO of 98,94 times whereas for ITO it is PT PCAR with the ratios of 17.93 times. On the profitability ratio, PT MPLT has the best financial performance for NPM of 16.15% while for ROI is PT KMDS with a ratio of 20.57%. As for the indicators used in this study, PT KMDS is the company with the best financial performance.